Controlling Citrus Huanglongbing: Green Sustainable Development Route Is the Future - Li, Xue; Ruan, Huaqin; Zhou, Chengqian; Meng, Xiangchun; Chen, Wenli (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is the most severe bacterial disease of citrus crops caused by Candidatus Liberibacter spp. It causes a reduction in fruit yield, poor fruit quality, and even plants death. Due to the lack of effective medicine, HLB is also called citrus “AIDS.” Currently, it is essential for the prevention and control of HLB to use antibiotics and pesticides while reducing the spread of HLB by cultivating pathogen-free seedlings, removing disease trees, and killing Asian citrus psyllid (ACP). New compounds [e.g., antimicrobial peptides (AMPs) and nanoemulsions] with higher effectiveness and less toxicity were also found and they have made significant achievements. However, further evaluation is required before these new antimicrobial agents can be used commercially. In this review, we mainly introduced the current strategies from the aspects of physical, chemical, and biological and discussed their environmental impacts. We also proposed a green and ecological strategy for controlling HLB basing on the existing methods and previous research results.